Students’ Experiences with Adaptive Learning Materials in Enhancing Spoken English and Self-Confidence - Maria Ramasari; Ardayati Ardayati (JURNAL PERSPEKTIF PENDIDIKAN, 2026)
This study explores students’ experiences in using adaptive learning materials to enhance their spoken English proficiency and self-confidence. This research employed a qualitative case study design involving twenty-seven students from the English Department of the University of PGRI Silampari, Indonesia. Data were collected through semi-structured interviews, classroom observations, and reflective learning journals during a speaking course in which adaptive learning materials were implemented. The collected data were analysed using thematic analysis to identify emerging patterns in students’ experiences. The findings reveal three major themes. First, adaptive learning materials increased students’ engagement in speaking activities by providing contextualized and interactive tasks. Second, the materials facilitated gradual improvement in students’ speaking abilities through structured practice and collaborative interaction. Third, students reported significant improvement in their self-confidence as the adaptive tasks reduced anxiety and encouraged active participation. The study highlights the pedagogical potential of adaptive learning materials in supporting both linguistic competence and affective development in EFL speaking classrooms. The findings contribute to the growing body of research on learner-centered instructional design and provide practical implications for lecturers seeking to improve speaking instruction in higher education contexts.